Potensi Ruang Terbuka di Sepanjang Bantaran Sungai Batang Lembang Kota Solok - Listen Prima; Abdurrachman Arief; Mutiara Winanda; Siti Saskia Adela (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
Geographically, Batang Lembang River is located in Solok Regency and Solok City, and is the largest and longest river in Solok Regency and City. In addition, there are several open spaces along the banks of the Batang Lembang River, Solok City which have the potential for city development; the first location is Merdeka Square, the second location is beside the army hospital, the third location is beside the Al-Hidayah Mosque, and the fourth location is Syech Kukut Park, Solok City. This study uses a descriptive method through surveys and then data analysis with Archgis and JMP application applications with the aim of knowing the type of potential or function of green open space in the research area so that it can be developed based on the function to create a sustainable urban environment. Based on the surveys result and data analysis from four green open spaces, it can be seen that the type of potential or function of the green open space with socio-cultural functions, then three green open spaces namely the first, second, and fourth locations can be used for aesthetic functions, and also the fourth location can be used. with an economic function to accommodate the activities or buying and selling activities of the surrounding community. Therefore, the result would be an input to the local government or related party to set the development local program.